The Impact of Warm Pool SST and General Circulation on Increased Temperature over the Tibetan Plateau - 王澄海 余莲 黄波 (Advances in atmospheric sciences, 2012)
In this paper, the possible reason of Tibetan Plateau （TP） temperature increasing was investigated. An increase in T min （minimum temperature） plays a robust role in increased TP temperature, which is strongly related to SST over the warm pool of the western Pacific Ocean, the subtropical westerly jet stream （SWJ）, and the tropical easterly upper jet stream （TEJ）, and the 200hPa zonal wind in East Asia. Composite analysis of the effects of SST, SWJ, and TEJ on pre and postabrupt changes in T a （annual temperature） and T min over the TP shows remarkable differences in SST, SWJ, and TEJ. A lag correlation between T a /T min , SST, and SWJ/TEJ shows that changes in SST occur ahead of changes in T a /T min by approximately one to three seasons. Partial correlations between T a /T min , SST, and SWJ/TEJ show that the effect of SWJ on T a /T min is more significant than the effect of SST. Furthermore, simulations with a community atmospheric model （CAM3.0） were performed, showing a remarkable increase in T a over the TP when the SST increased by 0.5 ？ C. The main increase in T a and T min in the TP can be attributed to changes in SWJ. A possible mechanism is that changes in SST force the TEJ to weaken, move south, and lead to increased SWJ and movement of SWJ northward. Finally, changes in the intensity and location of the SWJ cause an increase in T a /T min . It appears that TP warming is governed primarily by coherent TEJ and SWJ variations that act as the atmospheric bridges to remote SSTs in warmpool forcing.